2015
DOI: 10.5120/20773-3252
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Technique for Deriving Encryption Keys from Fingerprints to Secure Fingerprint Templates in Unimodal Biometric Systems

Abstract: In this study, we reviewed biometric template protection schemes in subsisting literature and established that there is no reliable, efficacious and foolproof technique that assures diversity, revocability, security and optimal performance as is required of an ideal biometric template security scheme. This status of affairs motivated us to contrivance an approach that derives biometric encryption keys from biometric fingerprint templates. The technique we proposed involves a two-step enrollment and authenticat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…These codes will be stored separately from other data. This technology has been used successfully in other projects in Kenya [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…These codes will be stored separately from other data. This technology has been used successfully in other projects in Kenya [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…A binary image input to the thinning process produces another binary image in which the ridges and valleys are only one pixel wide whereas the connectivity and the original contour must be maintained ( Ji et al, 2007). The most important task to recognize an individual is possible if we have his minutiae features (Mwema et al, 2015). The most widely used features are edge and bifurcation which has to be properly extracted from image (Das, 2012).…”
Section: Amjadmentioning
confidence: 99%
“…Reportedly, there are eight different types of attacks that has been carried out on various biometric systems. In order to counter such attacks, we found that mostly systems try to secure their fingerprint templates (Mwema et al, 2015). A two-stage features enrolment and validation process uses fingerprint features and a secret key which is also derived from another template to scramble the features and then store them in the database (Das, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%